Efficient "Click"‐Dendrimer‐Supported Synergistic Bimetallic Nanocatalysis for Hydrogen Evolution by Sodium Borohydride Hydrolysis. Issue 9 (8th April 2019) - Kang, Naixin; Djeda, Rodrigue; Wang, Qi; Fu, Fangyu; Ruiz, Jaime; Pozzo, Jean‐Luc; Astruc, Didier
Abstract: Hydrogen is efficiently generated upon "click" dendrimer‐supported catalysis of NaBH4 hydrolysis by a series mono‐ and bimetallic nanoparticles (NPs) of the late transition metals. Among the monometallic NPs, PtNPs show the best performances, Co being the best first‐raw transition metal. A remarkable synergy between Pt and Co in Pt/CoNP@dendrimer is also disclosed, compared with various other bimetallic NP catalysts, achieving a TOF of 303 molH2  ⋅ molcatal. −1  ⋅ min −1 when the ratio of Pt to Co is 1 : 1. In the presence of NaOH, the catalytic activity is boosted for all monometallic NPs except PtNPs, but NaOH exerted a negative influence on the bimetallic NP catalysts. The kinetic studies with the catalyst Pt1 Co1 NP@dendrimer involve in particular a primary kinetic isotope effect kD / k H =3.41 obtained for the hydrolysis reaction with D2 O, suggesting that O−H bond cleavage of water is involved in the rate‐determining step, and an overall reaction mechanism is proposed. Abstract : Playing together : In H2 delivery from NaBH4 hydrolysis, among mono‐ and bimetallic late transition metal nanoparticle (NP) catalysts stabilized by a click dendrimer, the best catalyst Co1Pt1 NPs shows a very positive synergy between Co and Pt in Co1Pt1 alloy improving the pure Pt nanocatalyst. Kinetics data including in particular a primary kinetic isotope effect with D2 O suggest concerted B−H and water O−H cleavage in the rate‐determining step.